High-throughput screening of stable and efficient double inorganic halide perovskite materials by DFT - Diao, Xinfeng; Diao, Yongxin; Tang, Yanlin; Zhao, Gangling; Gu, Qinzhong; Xie, Yu; Shi, Yebai; Zhu, Ping; Zhang, Liang (Scientific reports, 2022)
Perovskite solar cells have become the most promising third-generation solar cells because of their superior physical–chemical properties and high photoelectric conversion efficiency. However, the current obstacles to commercialization of perovskite solar cells are their poor stability and harmful elements. How to find high-efficiency, high-stability and non-toxic perovskite materials from thousands of possible perovskite crystals is the key to solve this problem. In this paper, the inorganic halide double perovskite A 2 BX 6 and its crystal structure are considered, and the data mining algorithm in informatics is introduced into the high-throughput computing data to analyze various elements in nature to study the perovskite materials that can meet the requirements of high performance. The photoelectric conversion properties and stability of 42 inorganic double perovskite materials are studied based on density functional theory (DFT). The results show that the tolerance factors of 39 crystals are between 0.8 and 1.10, indicating that these crystals have stable perovskite structure. In addition, the dielectric function, PDOS, elastic modulus, shear modulus and poison’s ratio of these crystals are analyzed. According to the above theoretical simulation results, three candidate materials for ideal light absorption are presented. This can provide a theoretical basis for the industrial application of perovskite solar cells.